Hasanlu V : The Late Bronze and Iron I Periods - Danti, Michael D. (Book collections on Project MUSE., 2013)
This book provides archaeologists with a more accurate chronology of Hasanlu, the largest and arguably the most important archaeological site in the Gadar River Valley of northwestern Iran. This revised chronology introduces Hasanlu Periods VIa, V, and IVc for the first time. Based on new findings, the report overturns current constructions of the origins of the archaeological culture in Hasanlu, which sought to link the Monochrome Burnished Ware Horizon (formerly known as the Early Western Grey Ware Horizon) to the migration of new peoples into western Iran in the later second millennium B.C. This book shows instead that the Monochrome Burnished Ware Horizon developed gradually from indigenous traditions. This reappraisal has important implications for our understanding of Indo-Iranian migrations into the Zagros region.